Simulated Microgravity Altered the Metabolism of Loureirin B and the Expression of Major Cytochrome P450 in Liver of Rats - Chen, Bo; Guo, Jingjing; Wang, Shibo; Kang, Liting; Deng, Yulin; Li, Yujuan (Frontiers in Pharmacology, 2018)
Loureirin B (LB) is the marker compound of dragon blood (DB), which exhibits great potentials in protecting astronauts’ health against radiation and simulated microgravity (SM). Pharmacokinetics of LB is reported to be significantly altered by SM. Here, we investigated key metabolic features of LB in rat liver microsome (RLM) and the effects of SM on LB metabolism as well as on expression of major hepatic cytochrome P450 (CYP450) isoforms. 10 metabolites were tentatively identified based on fragmentation pathways using LC-MS/MS method and elimination kinetics of LB followed a typical Michaelis-Menton equation (Vmax was 1.32 μg/min/mg and Km was 13.33 μg/mL). CYP1A2, CYP2C11, CYP2D1 and CYP3A2 were involved in the metabolism of LB and the relative strength was: CYP3A2 > CYP2C11 > CYP2D1 > CYP1A2. Comparative studies suggested that elimination of LB in RLM was remarkably increased by 3-day and 14-day SM, and the generation of identified metabolites was affected as well. Additionally, 3-day and 14-day SM showed obvious regulatory effects on the expression of major CYP450 isoforms, which might contribute to the increased elimination of LB. The data provided supports for the application of DB as a protective agent and the reasonable use of current medications metabolized by hepatic CYP450 in space missions.